The Influence of Selling Price Pricing, Margin Level, Product Quality, Shariah Marketing, Collateral, Product Knowledge and Risk on Member’s Interest in Using Murabahah Financing - Puspitasari, Cici; Jayanto, Prabowo Yudo (Universitas Negeri Semarang, 2016)
Penelitian ini bertujuan untuk menguji dan menganalisis pengaruh penetapan harga jual, tingkat margin, kualitas produk, marketing syari’ah, agunan, pengetahuan produk, dan risiko terhadap minat anggota menggunakan pembiayaan murabahah di BMT Kota Semarang. Sampel dalam penelitian ini diperoleh melalui kuesioner kepada 100 anggota yang menggunakan pembiayaan murabahah di BMT Kota Semarang. Metode pengambilan sampel yang digunakan adalah purposive sampling. Analisis data dalam penelitian ini menggunakan SEM dengan alat analisis SmartPLS 3,0. Hasil penelitian ini menunjukkan bahwa penetapan harga jual, kualitas produk, marketing syari’ah, dan pengetahuan produk memiliki hubungan positif dan signifikan terhadap minat anggota menggunakan pembiayaan murabahah. Variabel tingkat margin, agunan, dan risiko tidak berpengaruh terhadap minat anggota menggunakan pembiayaan murabahah. Saran bagi peneliti selanjutnya diharapkan memperluas ruang lingkup penelitian, misalnya pengambilan sampel seluruh BMT di Kota Semarang The purpose of this study was to examine and analyze the selling price pricing, margin level, quality of product, syari’ah marketing, collateral, product knowledge, and risk toward member’s interest in using murabahah financing in BMT Semarang city. The sample obtained by questionnaire was 100 respondents who were using murabahah financing in BMT Semarang city. Sampling method used purposive sampling. Analysis method used in this research was Structural Equation Modeling (SEM) with Partial Least Square (PLS) Path Modeling and analysis tool SmartPLS 3.0. Partial Least Square (PLS). The result of this research shows that selling price pricing, quality of product, syari’ah marketing, and product knowledge had positive and significant correlation toward member’s interest in using murabahah financing. The variable of margin level, collateral, and risk did not influence to member’s interest in using murabahah financing. The researcher suggests to the next researchers to add other independent variables which can strengthen or weaken the influence to dependent variables and widen the range of research, for example the sample is obtained from all of the BMT in Semarang city.